THE EFFECTIVENESS OF USING VISUAL AUDITORY KINESTETIC IN TEACHING READING FOR JUNIOR HIGH SCHOOL STUDENTS - Ajeng, Galuh Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2015)
This experimental research is conducted at SMP Kristen Kalam Kudus Surakarta, from December 2011 to June 2012. The sample of the research is two classes; one class is treated as experimental class taught by using visual auditory kinestetic and one classis treated as control class taught by using direct instruction. Each of them consisted of 28 students. The data are in the form of quantitative data that are taken from reading test. The data of reading test are used to know the students’ reading ability. The data of reading test are the scores of students’ reading test that was administered after having eight times treatments for each class. The researcher analyzes the data using t-test formula (SPSS for windows 17.0). Based on the result of data analysis, the research finding states that visual auditory kinesteticis more effective than direct instruction to teach reading for Junior High School students. Based on these research findings, it can be concluded that visual auditory kinesteticis an effective method to improve students’ reading ability. Ideally, visual auditory kinestetic has to be implemented in the class in order to achieve optimal result. By applying this method, the teachers have some roles. They are guiding, motivating,monitoring and help the students when they are doing some activities about reading. It can help the Junior High School students to become more independent, strategic and motivated readers.